Theoretical Analysis and Performance Comparison of multi-carrier Waveforms for 5G Wireless Applications - Mestoui, Jamal; El Ghzaoui, Mohammed (International Journal of Integrated Engineering, 2021)
5G wireless technology is a new wireless communication system that must meet different complementary needs: high data rate for mobile services, low energy consumption and long-range for connected objects, low latency to ensure real-time communication for critical applications and high spectral efficiency to improve the overall system capacity. The waveforms and associated signals processing, present a real challenge in the implementation for each generation of wireless communication networks. This paper presents the diverse waveforms candidate for 5G systems, including: CE-OFDM (Constant Envelope OFDM), Filter-Bank Multi Carrier (FBMC), Universal Filtered Multi-Carrier (UFMC) and Filtered OFDM (F-OFDM). In this work, simulations are carried out in order to compare the performance of the OFDM, CE-OFDM, F-OFDM, UFMC and FBMC in terms of Power spectral density (PSD) and of Bit Error Rate (BER). It has been demonstrated that (CE-OFDM), constitutes a more efficient solution in terms of energy consumption than OFDM signal. Moreover, the (F-OFDM), (UFMC) and (FBMC) could constitute a more efficient solution in terms of power spectral density, spectral efficiency and bit error rates. In fact, CE-OFDM reduces the Peak to Average Power Ratio (PAPR) associated with OFDM system, FBMC is a method of improving out-of-band (OOB) characteristic by filtering each subcarrier and resisting the inter-carrier interference (ICI). While, UFMC offers a high spectral efficiency compared to OFDM.